EFFECT OF LAUGHTER THERAPY ON DEPRESSION LEVEL IN ELDERLY IN A NURSING HOME, NORTH SUMATRA, INDONESIA - Rinco Siregar; Rumondang Gultom (Belitung Raya Foundation, Indonesia, 2019)
Background: Depression level among elderly remains high in Indonesia. One of efforts to decrease depression is laughter therapy, which is assumed able to lower depression. Objective: This study aimed to examine the effect of laughter therapy on depression level in elderly at Nursing Home of Binjai Integrated Social Service Unit for the Elderly, North Sumatra, Indonesia. Methods: This was a quasi-experimental study with pretest posttest with control group design. Forty-two participants were selected using a purposive sampling, with twenty-one participants were randomly assigned in each group. An experimental group received one-hour laughter therapy for 3 times a week in 4 weeks, and a control group received usual care. Depression was measured using Geriatric Depression Scale-15. Data were collected from April to June 2018. Independent and dependent t-test were used for data analysis. Results: Findings revealed that the level of depression in elderly significantly decreased in the experimental group (p<.05), but there was no significant change of it in the control group (p=.648). Between the two groups, there was a significant difference in depression level in elderly (p<.05). Conclusion: Laughter therapy could reduce depression among elderly. Therefore, this therapy can be used as one of interventions in nursing practice, especially at nursing homes.